PATHOGENESIS OF FACTOR VII DEFICIENCY - Mirzaeva Dinara; Umarova Tamila Abdufattoevna; Mansurov Shoxrux Karimovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Factor VII (FVII) deficiency is a bleeding disorder with an autosomal recessive inheritance pattern, in which reduced FVII activity in plasma is caused by quantitative or qualitative defects in the structure of the FVII protein. The global prevalence is approximately 1 patient per 500,000 population. About 99% of FVII circulates in plasma as an inactive zymogen, and only 1% is in the active form (FVIIa). The active form binds at the site of vascular injury with tissue factor (TF). The TF–FVIIa complex promotes further generation of FVIIa from the FVII zymogen and activates coagulation factors X (FX) and IX (FIX), which are involved in thrombin generation during the initiation phase of blood coagulation.